Implementation of Transformational Leadership in Improving Teacher Performance in Secondary Schools - Irmawati Thahir; Evy Segarawati Ampry; Firdaus Firdaus (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the implementation of transformational leadership models by school principals and their influence on improving teacher performance in secondary schools. The research adopts a mixed-method approach, integrating both qualitative and quantitative data to provide a comprehensive understanding. The study was conducted in 15 secondary schools, involving a total of 245 respondents consisting of school principals and teachers. Data collection techniques included the use of questionnaires to gather quantitative data, alongside in-depth interviews and direct observations for qualitative insights. The results reveal that transformational leadership—particularly through its core components of intellectual stimulation, inspirational motivation, individualized consideration, and idealized influence—has a significant positive impact on teacher performance. These leadership behaviors were found to enhance teaching quality, increase teacher professional commitment, and improve overall job satisfaction among educators. Additionally, the study highlights the role of school culture and the professional learning environment as mediating factors in the effectiveness of transformational leadership. The findings underscore the importance of implementing structured leadership development programs for school principals. By equipping school leaders with transformational leadership skills, educational institutions can foster more supportive and dynamic teaching environments that ultimately lead to better learning outcomes. These insights are particularly relevant for policymakers and educational administrators who are seeking sustainable strategies to improve school performance through leadership practices. In conclusion, transformational leadership stands out as a vital leadership style that not only motivates and empowers teachers but also contributes significantly to the institutional development of schools.